Divergent roles of herbivory in eutrophying forests - Segar, Josiane; Pereira, Henrique M.; Baeten, Lander; Bernhardt-Römermann, Markus; De Frenne, Pieter; Fernández, Néstor; Gilliam, Frank S.; Lenoir, Jonathan; Ortmann-Ajkai, Adrienne; Verheyen, Kris; Waller, Donald; Teleki, Balázs; et al. (Nature Communications, 2022)
Ungulate populations are increasing across Europe with important implications for forest plant communities. Concurrently, atmospheric nitrogen (N) deposition continues to eutrophicate forests, threatening many rare, often more nutrient-efficient, plant species. These pressures may critically interact to shape biodiversity as in grassland and tundra systems, yet any potential interactions in forests remain poorly understood. Here, we combined vegetation resurveys from 52 sites across 13 European countries to test how changes in ungulate herbivory and eutrophication drive long-term changes in forest understorey communities. Increases in herbivory were associated with elevated temporal species turnover, however, identities of winner and loser species depended on N levels. Under low levels of N-deposition, herbivory favored threatened and small-ranged species while reducing the proportion of non-native and nutrient-demanding species. Yet all these trends were reversed under high levels of N-deposition. Herbivores also reduced shrub cover, likely exacerbating N effects by increasing light levels in the understorey. Eutrophication levels may therefore determine whether herbivory acts as a catalyst for the “N time bomb” or as a conservation tool in temperate forests.